2012
DOI: 10.1007/s12665-012-1854-1
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic mineralogy and its implication of contemporary coastal sediments from South China

Abstract: Magnetic parameters have been widely used as a rapid, cost-effective, and non-destructive method. To assess whether their magnetic properties reflect the development history in the Pearl River Delta, three sediment cores collected from South China coastal waters were selected for magnetic research. The results indicate that the predominant ferrimagnetic mineral is magnetite, with an additional smaller amount of surprisingly high-coercive greigite. Fine-grained superparamagnetic and singledomain particles of ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 59 publications
0
5
1
Order By: Relevance
“…The significant positive correlation between χ lf and SIRM ( Figure 7B) indicated that the variation of these two parameters was largely controlled by a common effect of type and concentration of magnetic minerals. Differed from many previous studies (Yu and Oldfield, 1989;Ouyang et al, 2013), no obvious correlation was appeared between χ lf and χ fd % (Figure 7A), indicating that superparamagnetic (SP) particles were not the main controller for magnetic susceptibility. However, some superparamagnetic (SP) magnetite particles might be also appeared within the studied sediments due to relatively high average value of χ fd (average 4.54 × 10 −9 m 3 /kg) and significant paramagnetic signals during hysteresis measurements ( Figure 3B).…”
Section: Origin Of Magnetic Particlescontrasting
confidence: 77%
“…The significant positive correlation between χ lf and SIRM ( Figure 7B) indicated that the variation of these two parameters was largely controlled by a common effect of type and concentration of magnetic minerals. Differed from many previous studies (Yu and Oldfield, 1989;Ouyang et al, 2013), no obvious correlation was appeared between χ lf and χ fd % (Figure 7A), indicating that superparamagnetic (SP) particles were not the main controller for magnetic susceptibility. However, some superparamagnetic (SP) magnetite particles might be also appeared within the studied sediments due to relatively high average value of χ fd (average 4.54 × 10 −9 m 3 /kg) and significant paramagnetic signals during hysteresis measurements ( Figure 3B).…”
Section: Origin Of Magnetic Particlescontrasting
confidence: 77%
“…The last two have higher concentrations in hematite although the magnetic signal of the two northernmost sites in the northern river (PR09 and PR10) is also dominated by magnetites. No sulphides (greigite) are found in these sediments in contrast with sedimentary cores located off the Pearl River delta and in the sedimentary tongue along the coast [ Ouyang et al ., ]. The latter may have therefore suffered from some degree of diagenesis in the presence of organic matter, obviously not affecting the river sediments.…”
Section: Discussionmentioning
confidence: 99%
“…interval in PC338 (Figure e). These cores lie to the northeast of PC338 and are mostly supplied by the Pearl and Taiwan Rivers, with stable and relatively high magnetite contents compared to hematite (Kissel et al, ; Ouyang et al, ). For most surficial sediments, Red River S −300 values (0.7–0.9) are lower than those of the Pearl (0.85–1) and Taiwan Rivers (>0.9), which indicates relatively high hematite contents for the Red River (Kissel et al, ; Nguyen et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The magnetic properties of SCS sediments are analyzed in combination with geochemical and grain size data that are sensitive to paleoclimate variations (e.g., Bloemendal et al, 1988;Boulay et al, 2003;Kars et al, 2017;Kissel et al, 2003;Wei et al, 2004). Our results are also compared with magnetic property data for sediments from adjacent rivers and estuaries (Kissel et al, 2016Nguyen et al, 2016;Ouyang et al, 2013Ouyang et al, , 2017.…”
Section: Key Pointsmentioning
confidence: 99%